Assessment of occlusive disease of lower extremity arteries on the basis of anatomic region: Value of 128-slice multidetector CT angiography in comparison with digital subtraction angiography - Pangeni, Roshan; Han, Ping; Pan, Feng; Lamsal, Laxmi Pangeni; Zhang, Zhen; Yu, Jie; Rizal, Rajiv (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: The Previous studies of multidetector CT (MDCT) of the lower extremities for the detection of peripheral vascular disease showed high diagnostic accuracy but were performed with older generation systems. Our study aimed at assessing the diagnostic value of 128 MDCTA compared with that of digital subtraction angiography (DSA) in the grading of focal arterial disease of lower extremity arteries on the basis of anatomic regions. Materials & Methods: Forty-two patients with peripheral arterial occlusive diseases underwent both MDCTA and DSA. Lower extremity arteries depicted at MDCTA and DSA were graded separately for the degree of stenosis into 3 anatomic regions and 33 segments. Grading by MDCTA and DSA was done independently. Homogeneity analysis was used between MDCTA and DSA measurements in each patient. The sensitivity, specificity, positive predictive value and negative predictive value for detection of stenotic lesions were calculated for all anatomic regions, with findings at DSA used as the reference standard. Results: No statistically significant difference (P>.05) between DSA and MDCTA was present in Aorto-iliac and poplitiofemoral regions while there was statistically significant difference (P<.05) in the infrapopliteal region. The Sensitivity, Specificity, Positive Predictive Value and Negative Predictive Value based on a reading of MDCTA were 84.3%, 93.8%, 89.4% and 90.6% for aorto-iliac 86.6%, 94.7%, 84.1% and 94.7% for poplitiofemoral and 95.7%, 86.1%, 85.6% and 95.9% for infra-popliteal region respectively. Conclusion: MDCTA is excellent alternative in diagnosing lower extremity arterial occlusive diseases above the knee. DSA remains better on illustrating distal runoff vessels.